Beyond The Classroom: 3D Printing - Kansas State University, K-State First (Kansas State University. K-State First., 2016)
A poster promoting the presentation "3D Printing" at Kansas State University, hosted by Jahvelle Rhone, Information Technology Coordinator with the Information Technology Assistance Center, on September 27, 2016 at Wefald Hall. The session taught the basics of 3D printing.
Keywords: Beyond The Classroom; Events; Engagement; Community building; Application of learning; 3D printing; Posters